2023
DOI: 10.1038/s41586-023-06675-4
|View full text |Cite
|
Sign up to set email alerts
|

Mouse genome rewriting and tailoring of three important disease loci

Weimin Zhang,
Ilona Golynker,
Ran Brosh
et al.

Abstract: Genetically engineered mouse models (GEMMs) help us to understand human pathologies and develop new therapies, yet faithfully recapitulating human diseases in mice is challenging. Advances in genomics have highlighted the importance of non-coding regulatory genome sequences, which control spatiotemporal gene expression patterns and splicing in many human diseases1,2. Including regulatory extensive genomic regions, which requires large-scale genome engineering, should enhance the quality of disease modelling. E… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 49 publications
(59 reference statements)
1
4
0
Order By: Relevance
“…Mice are naturally resistant to SARS-CoV-2; whereas a previously made engineered human ACE2 mouse model expressing too much ACE2 protein on the cell surface resulted in the mice dying too fast from COVID ( 2 ). In contrast, the newly engineered mouse model had mild infection symptoms more consistent with those observed in humans ( 1 ). Moreover, the cell and tissue expression patterns more accurately reflected those found in humans, with ACE2 now found in the mouse testis and expressed at lower levels in the lung.…”
supporting
confidence: 58%
See 1 more Smart Citation
“…Mice are naturally resistant to SARS-CoV-2; whereas a previously made engineered human ACE2 mouse model expressing too much ACE2 protein on the cell surface resulted in the mice dying too fast from COVID ( 2 ). In contrast, the newly engineered mouse model had mild infection symptoms more consistent with those observed in humans ( 1 ). Moreover, the cell and tissue expression patterns more accurately reflected those found in humans, with ACE2 now found in the mouse testis and expressed at lower levels in the lung.…”
supporting
confidence: 58%
“…Now, Zhang et al. ( 1 ), working in Jef Boeke’s group at New York University Grossman School of Medicine in the USA, developed a way to study these human regulatory codes by genetically ‘writing’ as much as 180 kilobases of human DNA in place of the corresponding mouse regions in mouse embryonic stem (ES) cells.…”
mentioning
confidence: 99%
“…For example, during the COVID-19 pandemic, the generation of the SARS-CoV-2 genome has the potential to promote the unraveling of disease mechanisms and the development of vaccines [88]. Zhang et al [31] constructed genetically engineered mouse models by introducing 116 kb and 180 kb humanized ACE2 loci in S. cerevisiae, which, when compared to the existing K18-hACE2 models, presented milder symptoms upon exposure to SARS-CoV-2 and more closely resembled human infection models.…”
Section: Discussionmentioning
confidence: 99%
“…To better replicate human ACE2 expression dynamics in mice, Zhang et al [ 129 ] recently reported a novel genome writing method to generate humanized ACE2 mice. These mice express the regulatory components and splice isoforms of human ACE2 at levels that mimic expression in people, so are potentially a more physiologically relevant mouse model of COVID-19.…”
Section: Animal Models Of Covid-19mentioning
confidence: 99%